MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI LKPD BERBASIS AUGMENTED REALITY SISWA SD NEGERI 77 PAREPARE - Zaid Zainal; Nur Ilmi; Priti Mainna (MES: Journal of Mathematics Education and Science, 2025)
This study aims to determine the improvement of the process and learning outcomes of mathematics in the volume of building space through the use of student worksheet based Augmented Reality for students in grade V of UPTD SD Negeri 77 Parepare. This research uses a qualitative approach and the type of research used is Classroom Action Research. The focus of this research is the learning process and learning outcomes. This research was carried out at UPTD SD Negeri 77 Parepare for the 2024/2025 school year with the subject of this research being 1 classroom teacher and 20 students consisting of 8 males and 12 females. The research was carried out in two cycles, each of which consisted of two meetings which included planning, implementation, observation, and reflection. The data collection techniques used are observation, tests and documentation. The data was analyzed using data condensation, data presentation, and conclusion drawing techniques. In cycle I, the results of the study showed that the learning process of teachers' activities and the learning process of students increased to the qualification of sufficient to good with a percentage of 73.33% to 86.66% and 72.59% to 78.66%. Then, the learning outcomes of students are at the Sufficient qualification with a percentage of 70%. Meanwhile, in the second cycle, it showed that the learning process of teachers' activities and the learning process of students increased to good qualifications with a percentage of 93.33% and 85.83% to 86.66%. Then, the learning outcomes of students increased to the good qualification with a percentage of 80%. So it can be concluded that using student worksheet based Augmented Reality in mathematics subjects can improve the learning process and learning outcomes of students in class V SD Negeri 77 Parepare.